2004
DOI: 10.1177/001698620404800304
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Motivational Characteristics of Adolescents Gifted in Mathematics: Comparisons Among Students With Different Types of Giftedness

Abstract: had a significant impact on the field of gifted education. With the transition, gifted education has shifted its emphasis from identifying youngsters with high intellectual ability to discovering a wide variety of specific talents in young people in its efforts to provide special educational opportunities to the gifted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 42 publications
8
51
0
10
Order By: Relevance
“…Computer simulations designed to help students practice perspective-taking often present problems from a variety of viewpoints (Tünzün, 2007). Hyperlinks or multi-nodal simulations stimulate nonlinear thinking, which in turn fosters sensitivity toward and appreciation of unusual, creative, and divergent approaches to problem solving by academically and creatively gifted students, who use more cognitive strategies while problem solving than average students (Hong & Aqui, 2004).…”
Section: Critical Thinking Skillsmentioning
confidence: 99%
“…Computer simulations designed to help students practice perspective-taking often present problems from a variety of viewpoints (Tünzün, 2007). Hyperlinks or multi-nodal simulations stimulate nonlinear thinking, which in turn fosters sensitivity toward and appreciation of unusual, creative, and divergent approaches to problem solving by academically and creatively gifted students, who use more cognitive strategies while problem solving than average students (Hong & Aqui, 2004).…”
Section: Critical Thinking Skillsmentioning
confidence: 99%
“…T. Bakanovienė (2010) tyrė matematikai gabių vaikų atpažinimo klausimus. Galima aptikti tyrimų, kuriuose analizuojama, kaip dalyvavimo matematiniuose konkursuose reiškinys yra susijęs su matematiniu ugdymu mokykloje (Gleason, 2008;Hong, Aqui, 2004;Kenderov, 2006;Subotnik, Miserandino, Olszewski-Kubilius, 2003;Webb, Lubinski, Benbow, 2000).…”
Section: Issn 1392-0340 E-issn 2029-0551unclassified
“…Daugybė autorių kaip itin svarų veiksnį, lemiantį domėjimąsi matematika, nurodo mokinių lytį (Gallagher, Kaufman, 2005;Hong, Aqui, 2004). Asmeninės savybės, tokios kaip asmenybės kryptingumas, nuostatos, vertybės, charakteris, pažinimo, emocijų, valios procesai neabejotinai itin stipriai veikia aukštus pasiekimus matematiniuose konkursuose.…”
Section: Matematikos Konkurso Pasirinkimą Lemiantys Veiksniaiunclassified
“…However, in their studies, Siegle and McCoach (2007) and Webb et al (2016) found gender didn't significantly predict self-efficacy in math and no gender differences were identified relative to writing self-efficacy. Finally, identified gifted students have generally reported higher levels of self-efficacy when compared to their non-identified peers (Hong & Aqui, 2004;Webb et al, 2016).…”
Section: Self-efficacymentioning
confidence: 95%